2021
DOI: 10.1002/acn3.51290
|View full text |Cite
|
Sign up to set email alerts
|

Selective vulnerability to atrophy in sporadic Creutzfeldt‐Jakob disease

Abstract: Objective: Identification of brain regions susceptible to quantifiable atrophy in sporadic Creutzfeldt-Jakob disease (sCJD) should allow for improved understanding of disease pathophysiology and development of structural biomarkers that might be useful in future treatment trials. Although brain atrophy is not usually present by visual assessment of MRIs in sCJD, we assessed whether using voxel-based morphometry (VBM) can detect group-wise brain atrophy in sCJD. Methods: 3T brain MRI data were analyzed with VBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 83 publications
1
5
0
Order By: Relevance
“…For the first time, we identified abnormally increased functional connectivity at rest in sCJD, both in the dorsal and ventral components of the DMN. Our multimodal analysis corroborates our atrophy‐based hypothesis that DMN areas are particularly vulnerable in sCJD (Younes et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For the first time, we identified abnormally increased functional connectivity at rest in sCJD, both in the dorsal and ventral components of the DMN. Our multimodal analysis corroborates our atrophy‐based hypothesis that DMN areas are particularly vulnerable in sCJD (Younes et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…Visual and quantitative assessments of diffusivity abnormalities in sCJD, although heterogeneous, generally show prominent involvement of the anterior cingulate, parieto-angular, retrosplenial, and middle temporal cortices Vitali et al, 2011) areas that are part of the Default Mode Network (DMN) (Alves et al, 2019;Buckner et al, 2008;Leech & Sharp, 2014). In a recent voxel-based morphometry study, we found selective atrophy in almost all regions part of DMN, further suggesting that DMN network could be a preferential site of involvement in prion disease (Younes et al, 2021).…”
Section: Introductionmentioning
confidence: 63%
“…It has recently been suggested that such propagation in neurodegenerative proteinopathies may involve trans‐neuronal spread of misfolded protein between interconnected brain regions and may therefore be spatially constrained by structural connectivity across the brain 36,44 . Whether because of increased susceptibility to PrP C misfolding, increased PrP Sc propagation, or increased vulnerability to PrP Sc related neuronal damage, our findings suggest that brain regions that show correlated levels of PRNP expression also define networks that have selective vulnerability to CJD pathology 45 …”
Section: Discussionmentioning
confidence: 62%
“…36,44 Whether because of increased susceptibility to PrP C misfolding, increased PrP Sc propagation, or increased vulnerability to PrP Sc related neuronal damage, our findings suggest that brain regions that show correlated levels of PRNP expression also define networks that have selective vulnerability to CJD pathology. 45 Our overall findings point to the importance of regional expression of PRNP in forming the genetic landscape on which the pathobiology of sCJD unfolds and raises the possibility that multiple genetic or environmental factors may be important in determining the regional characteristics of different sCJD subtypes. Currently, the specifics of these other factors are unknown.…”
Section: Discussionmentioning
confidence: 69%
“…The sensitivity of RT-QuIC for detecting MM1 and VV2 is high (96.3%) but can be negative for MM2 and VV1 subtypes ( 33 , 42 ). Younes et al reported that MM1, MV1, and VV2 are related to short duration/fast progression, while MV2, VV1, and MM2 are associated with long duration/slow progression ( 43 ). Our case series revealed that patients 3 and 4 were sCJD-MM1 but with an 8-month difference in survival length; patients 1 and 5 were diagnosed with sCJD-VV2 with similar survival durations, 8 vs. 6 months.…”
Section: Discussionmentioning
confidence: 99%